Endoplasmic reticulum chaperone GRP78 regulates macrophage function and insulin resistance in diet‐induced obesity. Issue 4 (5th January 2018) - Kim, Jong Hun; Lee, Eunjung; Friedline, Randall H.; Suk, Sujin; Jung, Dae Young; Dagdeviren, Sezin; Hu, Xiaodi; Inashima, Kunikazu; Noh, Hye Lim; Kwon, Jung Yeon; Nambu, Aya; Huh, Jun R.; et al.
Abstract : Obesity‐mediated inflammation is a major cause of insulin resistance, and macrophages play an important role in this process. The 78‐kDa glucose‐regulated protein (GRP78) is a major endoplasmic reticulum chaperone that modulates unfolded protein response (UPR), and mice with GRP78 heterozygosity were resistant to diet‐induced obesity. Here, we show that mice with macrophage‐selective ablation of GRP78 (Lyz‐GRP78 −/− )are protected from skeletal muscle insulin resistance without changes in obesity compared with wild‐type mice after 9 wk of high‐fat diet. GRP78‐deficient macrophages demonstrated adapted UPR with up‐regulation of activating transcription factor (ATF)‐4 and M2‐polarization markers. Diet‐induced adipose tissue inflammation was reduced, and bone marrow‐derived macrophages from Lyz‐GRP78 −/− mice demonstrated a selective increase in IL‐6 expression. Serum IL‐13 levels were elevated by >4‐fold in Lyz‐GRP78 −/− mice, and IL‐6 stimulated the myocyte expression of IL‐13 and IL‐13 receptor. Lastly, recombinant IL‐13 acutely increased glucose metabolism in Lyz‐GRP78 −/− mice. Taken together, our data indicate that GRP78 deficiency activates UPR by increasing ATF‐4, and promotes M2‐polarization of macrophages with a selective increase in IL‐6 secretion. Macrophage‐derived IL‐6 stimulates the myocyte expression of IL‐13 and regulates muscle glucose metabolism in a paracrine manner. Thus, our findings identify a novel crosstalk between macrophages and skeletal muscle in the modulation of obesity‐mediated insulin resistance.— Kim, J. H., Lee, E., Friedline, R. H., Suk, S., Jung, D. Y., Dagdeviren, S., Hu, X., Inashima, K., Noh, H. L., Kwon, J. Y., Nambu, A., Huh, J. R., Han, M. S., Davis, R. J., Lee, A. S., Lee, K. W., Kim, J. K. Endoplasmic reticulum chaperone GRP78 regulates macrophage function and insulin resistance in diet‐induced obesity. FASEB J. 32, 2292–2304 (2018). www.fasebj.org